(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to analyze the costs of antibiotic (AB) use at Thu Duc City Hospital (TDCH) in 2024. Methods: A cross-sectional descriptive study was conducted by collecting data on the costs of antibiotic use in treating patients covered by health insurance at TDCH from January to June 2024. Antibiotic costs were analyzed according to various factors, including drug classification, country of origin, route of administration, and drug components. Results: From January to June 2024, the total expenditure on antibiotics for insured patients at TDCH amounted to 14.4 billion VND. Of this, 55.2% was allocated to inpatient treatment and 44.8% to outpatient care. Antibiotics manufactured in Vietnam constituted 65.7% of the total, while combination antibiotics accounted for 51.9%. The proportion of antibiotic costs relative to total drug costs in inpatient care for the first and second quarters of 2024 was 22.9% and 21.8%, respectively, compared to 5.3% and 5.9% in outpatient care. Beta-lactams represented the largest proportion of antibiotic costs in both inpatient and outpatient settings, with inpatient care costs for Beta-lactams being 60.7% in the first quarter and 80.5% in the second quarter. Quinolones and Macrolides ranked second and third in terms of antibiotic expenditure. Conclusion: This analysis of quarterly antibiotic costs highlights significant temporal variations in antibiotic use patterns at TDCH in 2024. The findings provide hospital administrators with valuable insights to inform adjustments to drug management policies, ensuring more efficient resource allocation..